SOUND ELEMENTS AS INVISIBLE COMMUNICATORS IN THE FILM TWO DISTANT STRANGERS - Leonardus Aryo Gitoprakoso Widyarto; Siti Febrina Rahmadani; Silviana Amanda Aurelia Tahalea; Anita Armas (ISI Press Institut Seni Indonesia Surakarta, 2026)
The effectiveness of visual meaning in a film depends on the support of sound; hence, the interplay between visual and auditory elements forms the foundation for narrative development, emotional resonance, and audience interpretation. Accordingly, this study seeks to analyze the interplay between visual and auditory components, including ambiance, dialogue, sound effects, and background music, in enhancing the narrative in the film Two Distant Strangers. This study employs a qualitative approach, utilizing Roland Barthes' semiotics to analyze the meanings generated by the integration of visual and auditory design. The results demonstrate that atmosphere intensifies emotions of confusion, fear, frustration, and tension; dialogue, particularly when paired with music, enhances the audience's comprehension of the scene; sound effects accompanying character actions clarify the message of injustice; and background music aligns with the emotional tone of the scene, reinforcing the visual atmosphere. Well-designed music profoundly deepens emotional resonance, elucidates the narrative, and enhances the coherence of the film's overall cinematic experience.